THE EFFECT OF DISASTER MITIGATION LEARNING ON TOURISM STUDENTS' DISASTER KNOWLEDGE IN LOMBOK, INDONESIA - Mahmudah Budiatiningsih; Ihyana Hulfa; Maulana Malik Irsyad (INDONESIAN JOURNAL OF ENVIRONMENT AND DISASTER, 2026)
This study aims to explore the effect of disaster mitigation learning on tourism students' disaster knowledge. This quantitative study employs a one-group pretest-posttest quasi-experimental design to evaluate the effect of disaster mitigation education on the knowledge of tourism students. The population of this study consists of all students enrolled in the mandatory Disaster Mitigation course within the Tourism Diploma Program (DIII) at Universitas Mataram. The respondents were 94 college students, sampled by census. The assessments were conducted using a knowledge test questionnaire about disaster knowledge. The Wilcoxon Signed-Rank Test result showed the significance 0.000 that was less than 0.05, indicating a statistically significant difference between pretest and posttest score. The result showed that a semester-long disaster mitigation learning in Mataram University Tourism Study Program was proven to increase students’ knowledge about the types of disasters, disaster occurrence, risks in campus buildings and tourism destinations, disaster impacts, actions during disasters, and evacuation requirements.